Buckling behavior of large-scale thin-walled ellipsoidal head under internal pressure. (August 2019) - Li, K.; Zheng, J.; Liu, S.; Ge, H.; Sun, G.; Zhang, Z.; Gu, C.; Xu, P.
Abstract: Compressive stresses present in the knuckle of ellipsoidal heads subjected to internal pressure. The presence of such stresses may make buckling possible. In this study, we combine experimental and numerical methods to investigate the buckling behavior of large-scale thin-walled ellipsoidal heads. Buckling experiments were conducted on three thin large-scale ellipsoidal heads with diameters up to 5 m and thicknesses of 5.5 mm. Finite element models of the ellipsoidal heads with measured initial shapes were generated to simulate the buckling behavior, which is compatible with the experimental observation that one or more buckles first occur at local positions in the knuckle and more ones form progressively with increasing pressure. Furthermore, the buckles become smaller or even disappear at relatively higher pressure, indicating that buckling is self-limited. These buckling behaviors are explained by changes in compressive stresses and shapes of ellipsoidal heads. In addition, we performed numerical simulation to investigate the effects of material properties, radius-to-height ratio, diameter-to-thickness ratio, and shape imperfection on buckling behavior. Highlights: Buckling experiments are conducted on internally pressurized ellipsoidal heads with diameters up to 5 m. Buckling behavior is simulated by nonlinear FEM. Effects of material property, radius-height ratio, diameter-thickness ratio, and shape imperfection are investigated. Three basis buckling characteristics are summarized: locality, progressivity and self-limitation.